Enhancement in electrical and magnetic properties with Ti-doping in Bi0.5La0.5Fe0.5Mn0.5O3 - Singh R.; Gupta P.K.; Kumar S.; Joshi A.G.; Ghosh A.K.; Patil S.; Chatterjee S. (My University, 2025)
In this investigation, we have synthesized Bi0.5La0.5Fe05Mn0.5-xTixO3 (where x = 0 and 0.05) samples. The Rietveld refinement of X-ray diffraction (XRD) patterns shows that the systems crystallize in the orthorhombic phase with the Pnma space group. The observed Raman modes support the XRD results. The appearance of prominent A1-3 and weak E-2 modes in Bi0.5La0.5Fe0.5Mn0.45Ti0.05O3 indicates the presence of chemically more active Bi-O covalent bonds. Ferromagnetism of Bi0.5La0.5Fe0.5Mn0.5O3 is enhanced by Ti doping at the Mn-site, indicating that these particular samples might be interesting for device applications. © 2017 Author(s).